Byrudite, (Be, 〈)(V3+, Ti)3O6, a new mineral from the Byrud emerald mine, South Norway. (2nd January 2018) - Raade, G.; Balić-Žunić, T.; Stanley, C. J.
Abstract: Byrudite (IMA 2013-045, Raade et al ., 2013), with simplified formula (Be, 〈)(V 3+, Ti)3 O6, occurs in emerald-bearing syenitic pegmatites of Permian age at Byrud farm, Eidsvoll, Akershus, South Norway. It has a norbergite-type structure, Pnma, with a = 9.982(1), b = 8.502(1), c = 4.5480(6) Å, V = 385.97(9) Å3, Z = 4. The structure was refined to R 1 = 0.045 for 1413 unique reflections. Twinning occurs on {210}. The occupancy of the tetrahedral Be site refined to 0.84(1). The presence of Be was verified by secondary ion mass spectrometry but could not be quantified. Electron-microprobe analyses of the crystal used for structure determination gave the empirical formula (Be0.84 〈0.16 ) (V1.32 3+ Ti1.25 Cr0.29 Fe0.09 Al0.07 )Σ3.02 O6 . There is a strong inverse correlation between V and Cr. The ideal endmember formula is BeV2 3+ TiO6 . The mineral is black and opaque with a metallic lustre. Reflectance data in air are reported from 400 to 700 nm. The Commission on Ore Mineralogy required wavelengths are [ R 1, R 2 (λ in nm)]:16.6, 17.5(470), 16.7, 17.9(546), 16.8, 18.3(589) and 16.8, 18.6(650). The Mohs hardness is ∼7, based on indentation measurements. The mineral is brittle with an uneven fracture; cleavage is not present. D (calc.) = 4.35 g cm –3 for the empirical formula with 0.84 Be a.p.f.u. The strongest reflections of the calculated powder X-ray diffraction pattern are [ d in Å (Irel )( hkl )]: 3.721(72)(111), 2.965(100)(121), 2.561(50)(311), 2.464(41)(230), 2.167(24)(231), 1.681(34)(402), 1.671(66)(232), 1.435(23)(630).